A new species of the family Trochometridiidae (Acari: Heterostigmatina) associated with Paulusiella sp. (Coleoptera: Elateridae) from Iran - Mortazavi, Abdolazim; Hajiqanbar, Hamidreza; Saboori, Alireza (Zootaxa, 2011)
The mite species Trochometridium kermanicum Mortazavi & Hajiqanbar sp. nov. (Acari: Heterostigmatina: Trochometridiidae) associated with an elaterid beetle of the genus Paulusiella (Insecta: Coleoptera) is described from Iran. This is the first record of association between trochometridiid mites and beetles of the family Elateridae. The host range of the family Trochometridiidae is reviewed and a key to world genera and species is provided.